Mentorship - Platz, Joseph; Hyman, Neil (Clinics in Colon and Rectal Surgery, 2013)
The world of medicine is in a state of flux with major and substantive changes in its educational model. Students, residents, and junior attendings can no longer rely entirely on experiential development through clinical immersion. Instead, to attain similar levels of knowledge, technique, and situational comfort, there must be innovations in medical education that take advantage of the experience of mentors. Mentoring has been a part of medicine and surgery since the days of apprenticeship. Mentors must now teach more basic medicine than ever before and adapt to changes in the structure of medical education such as the use of simulation, yet still continue to foster career development among trainees and junior colleagues. For mentoring to succeed and benefit mentees, it must be supported. This patronage starts with each local university or hospital system but eventually must permeate the greater medical culture.
Keywords: mentorship; medical education; training; role model